Determinants Of the Production and Profitability of Audit Services in Tunisia - Mouna Hamza; Salma Damak; Khaled Hussainey (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Purpose – This paper aims to identify the significant determinants of the production and profitability of audit services in Tunisia. Design/methodology/approach – Based on a sample of 299 audit engagements from Tunisian audit firms and spanning the period from 2016 to 2018, the researchers used Ordinary Least Squares (OLS) regression estimation to test the research hypotheses. Subsequently, the researchers summarized the variables by using the Principal Component Analysis (PCA). Findings –The study's findings show a positive association between client size and audit effort and, more specifically, larger clients are found to be more profitable to audit firms. Interestingly, larger specialized audit firms assign more audit hours and are less profitable. The findings show, also, that audit firms are likely to perform fewer audit hours when they rely heavily on the client's system and when the work is conducted during the busy season. Also, more audit effort is required when the engagement is a new one and when the firm previously provided the client with non-audit services. Originality/Value – This study contributes to audit pricing literature by constructing models for the production and profitability of audit services by examining how a pre-determined audit fees framework affects an auditor's efforts and profits.
Keywords: M42; 650; Tunisia; Audit production; Audit profitability; Audit fees